The Morpho-Syntax of Suffix-i - Darlina, Lien (International Journal of Psychosocial Rehabilitation, 2020)
This research wants to describe that suffix-i have an ability to be attached to form derivative verb. The study based on the typological linguistic was recommended by Comrie (1988); Artawa (1988,2018). The result of this research shows that the ability of suffix-i can be attached to form basic derivative verb and it serve a big contribution in forming basic noun, adjective, precategory and to form verb. If Suffix-i can be atteched to form verb is called morphosyntaxis which serve as interface between mophology and syntaxis. Morphosytaxis is a process derivation that maintain the word class (class maintaining derivation) means the new lexeme derivation which have a same class with his based form, but change the meaning (changes the lexical identity) to release certain function who produce derivative clause which are the causative and applicative meanings. Based on that two problems, the research want to know how the suffix-i has an ability to be attached to form derivative verb?.